Statistical analysis on the effectiveness of short-term programs during COVID-19 pandemic: in the case of program Bijak Sifir 2020 / Nazihah Safie ... [et al.] - Safie, Nazihah; Zakaria, Syerrina; Abdul Malik, Siti Madhihah; Ismail, Nur Baini; Alias, Azwani; Idris, Ruwaidiah (2021)
At the start of 2020, the whole world faced the Covid-19 pandemic spreading across countries, including Malaysia. The pandemic caused the Malaysian government to take immediate action to declare a Movement Control order (MCO). This MCO has a severe impact on almost all sectors of Malaysia, including the economic, social, and education sectors. For primary school students to strengthen their mathematics skills, we believed that short programs significantly affect their performance during MCO implementation. This study was conducted to measure the primary school students' performance during MCO for the short-term Mathematics program by applying the Naimo method in improving students' understanding of the basics of multiplication. There were two sets of mathematics score data before and after the program considered in this study. The Mann-Whitney test was conducted to test whether there is any significant difference in performance between genders for both data sets. Meanwhile, the Wilcoxon Signed Rank test was conducted to evaluate student performance's significant difference before and after the program. It was found that there was a significant difference in students' performance before and after the program, increasing the performance after the program. Although this program is conducted for a short time, this face-to-face learning program is one factor that significantly impacts student performance. As we believed, face-to-face teaching and learning activities are still necessary for all education levels, especially at the primary level, even if it only involves a short period. Nonetheless, the hybrid platform of teaching and learning must be prepared due to the pandemic era's uncertainty.